2023
DOI: 10.7759/cureus.33427
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Yogic Intervention Improves Symptomatic Scale and Quality of Life by Reducing Inflammatory Cytokines and Oxidative Stress in Breast Cancer Patients Undergoing Chemotherapy and/or Radiotherapy: A Randomized Control Study

Abstract: Introduction: Inflammation has been associated with tumor proliferation and metastasis in breast cancer. Yoga is an ancient therapy that helps in reducing inflammation and improves the patient's quality of life (QoL) and fatigue. In the current study, we investigated the effects of long-term yogic intervention at different time points on the level of inflammatory cytokines and oxidative stress, along with the symptomatic scale and QoL in stage II/III breast cancer patients.Methods: Ninety-six stage II/III brea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“… 44 noted the opposite. In addition, the yoga group showed significant increases in the serum granulocyte colony-stimulating factor, 44 monocyte chemotactic protein-1, 44 and malondialdehyde levels, 42 and significant decreases in the serum IL-10, 40 anti-apoptotic gene P53, 41 and anti-apoptotic gene Bcl2 levels. 41 …”
Section: Resultsmentioning
confidence: 93%
See 4 more Smart Citations
“… 44 noted the opposite. In addition, the yoga group showed significant increases in the serum granulocyte colony-stimulating factor, 44 monocyte chemotactic protein-1, 44 and malondialdehyde levels, 42 and significant decreases in the serum IL-10, 40 anti-apoptotic gene P53, 41 and anti-apoptotic gene Bcl2 levels. 41 …”
Section: Resultsmentioning
confidence: 93%
“…Jain et al. 42 found that the decline in the TNF-α level in the yoga group was better than that in the control group at 48 weeks of follow-up. Huberty et al.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations